2022
DOI: 10.3390/plants11101375
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Medicinal Plant Species from Indonesia

Abstract: Over the past decade, plant DNA barcoding has emerged as a scientific breakthrough and is often used to help with species identification or as a taxonomical tool. DNA barcoding is very important in medicinal plant use, not only for identification purposes but also for the authentication of medicinal products. Here, a total of 61 Indonesian medicinal plant species from 30 families and a pair of ITS2, matK, rbcL, and trnL primers were used for a DNA barcoding study consisting of molecular and sequence analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
(72 reference statements)
1
10
0
Order By: Relevance
“…Therefore, in addition to improving the plant identification database, the DNA barcoding techniques has been well-employed to identify the biodiversity of medicinal plants in Indonesia. A group of researcher examined four distinct DNA barcoding regions-rbcL, ITS2, trnL, and matK-to identify 61 species of Indonesian medicinal plants, including two IUCN vulnerable (VU) species: the Aquilaria hirta and the Etlingera solaris (Cahyaningsih et al, 2022). Importantly, the results of this study also support the idea that DNA barcoding can be used to distinguish between pure extract of medicinal herbs compared to fake substitutes (Mishra et al, 2016).…”
Section: Indonesian Dna Barcode Research Trendsupporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, in addition to improving the plant identification database, the DNA barcoding techniques has been well-employed to identify the biodiversity of medicinal plants in Indonesia. A group of researcher examined four distinct DNA barcoding regions-rbcL, ITS2, trnL, and matK-to identify 61 species of Indonesian medicinal plants, including two IUCN vulnerable (VU) species: the Aquilaria hirta and the Etlingera solaris (Cahyaningsih et al, 2022). Importantly, the results of this study also support the idea that DNA barcoding can be used to distinguish between pure extract of medicinal herbs compared to fake substitutes (Mishra et al, 2016).…”
Section: Indonesian Dna Barcode Research Trendsupporting
confidence: 52%
“…In Indonesia, the use of DNA barcoding technique in the identification of flowering and medicinal plants has been increasing in recent years (Amandita et al, 2019;Cahyaningsih et al, 2022). Tropical rainforests of Sumatra in Indonesia provide an abundance of vegetation and wildlife (Basyuni et al, 2019;Breidenbach et al, 2018;Rambey et al, 2021).…”
Section: Indonesian Dna Barcode Research Trendmentioning
confidence: 99%
“…Previous studies have shown that the identification of DNA barcoding target species does not possess an optimal or flawless region. Despite this, they suggest the utilization of matK as the preferred barcode for identifying Indonesian medicinal plants [24,25]. Nevertheless, the use of DNA barcoding has been focused on a single region for most therapeutic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high quality of DNA extracted was a crucial step in any DNA molecular techniques. This DNA barcoding approach served as a new detection tool for identifying adulterated herbal medicinal products [4,16,18,25]. However, the DNA extraction from complex herbal products is challenging due to mixture of several of plants species that containing different polyphenols, alkaloids, and flavonoids [15] or mixed with other substance (talc/pharmaceutical excipients in their formulation, pigment, stabilizer, impurities, admixtures).…”
Section: Introductionmentioning
confidence: 99%